Sosialisasi Peran Pemuda Sebagai Kontrol Sosial Pada Kebijakan Gampong Lamreh - Iryadi, Irfan; Pratama, Riza Chatias (Jurnal Ragam Pengabdian, 2026)
Youth play a strategic role as a moral force, agents of change, and social control in community development, including in the formulation and oversight of village policies. However, many young people still have limited understanding of their legal standing, rights, obligations, and roles in village governance. This community service activity aimed to enhance youth knowledge and legal awareness regarding the concept of youth and their role as social control agents in village development policies. The activity was conducted in Lamreh Village, Darussalam District, Aceh Besar Regency, through three stages: preparation, implementation of legal outreach, and evaluation. The methods employed included legal counseling and interactive discussions involving village youth participants. Data were analyzed using a descriptive qualitative approach based on observations, discussions, and evaluation results obtained during the activity. The findings revealed an improvement in participants’ understanding of the concept of youth as regulated by Indonesian law, as well as increased legal awareness to participate in the formulation, supervision, and implementation of village policies. The activity also identified several challenges, including limited opportunities for youth participation and inadequate understanding of the role of youth in village governance. In conclusion, this legal outreach program effectively enhanced the capacity of youth as social control agents and contributed to the promotion of participatory, transparent, and accountable village governance.